The determinants of urban density: the Israeli case - Amnon Frenkel (European Regional Science Association (ERSA), 2002)
In the struggle against urban sprawl minimum requirements for urban density has become one of the promising tools in determining spatial planning policy, particularly in densely populated countries. This tool was first proposed in the Israel Master Plan 'Israel 2020' in the mid of the 1990s, as an instrument designed to control the conversion of open spaces into urban land use. It was subsequently adopted by the 'National Outline Plan no. 35'. It is reasonable to assume that urban density should vary spatially and be tailored to different types of urban localities. This study examines the variation in urban densities among 150 urban and rural localities in Israel. Two-way analysis of variances was employed in order to classify the localities into clusters based upon their urban density, size, location and spatial functionality. While most former classification studies use economic, social and demographic variables as a basis for their analysis, in the current study, the classification is based upon urban spatial structure and land uses. A regression model is then applied in order to examine the relationship between urban density and selected spatial variables. Population size, location, topography and the size of the built-up area were found to be significant explanatory variables. The findings obtained in the classification analysis and the identification of variables that affect urban density the most, could equip planning agencies with a benchmark for urban density norms. This study presents the variations in the urban density that characterise different clusters and identify the principal variables that should be taken into consideration in the formulation of spatial planning policy.
Keywords: 330